Bangkok found reflections on the city - Kerr, Alex 1952- (River Books, 2010)
Evocative and incisive, Bangkok Found looks deep within traditional culture to discover how Bangkok is like no other contemporary city. It's the book you read after you've seen the temples and enjoyed the nightlife - and then start to wonder where the mysterious appeal of Bangkok really lies. With wit and a wealth of anecdotes from Kerr's thirty years of experience in Thailand,Bangkok Found,sequel to his award-winning Lost Japan,takes you on a journey to the essential and the quirky, the factual and the mythical. In this series of meditations on the city, old culture meets global fusion in the crossroads that is Bangkok.